First Human Study of the Investigational Sedative and Anesthetic Drug AZD3043: A Dose-Escalation Trial to Assess the Safety, Pharmacokinetics, and Efficacy of a 30-Minute Infusion in Healthy Male Volunteers. (October 2015) - Kalman, Sigridur; Koch, Pauline; Ahlén, Kjell; Kanes, Stephen J.; Barassin, Stéphane; Björnsson, Marcus A.; Norberg, Åke
Abstract : BACKGROUND: AZD3043 is a positive allosteric modulator of the γ-aminobutyric acid type A receptor that is rapidly metabolized to an inactive metabolite by esterases present in blood and liver. Preclinical results suggest that AZD3043 has the potential as a short-acting IV sedative/anesthetic drug with rapid and predictable recovery characteristics and a favorable safety and tolerability profile. METHODS: Our primary objective in this phase 1, single-center, open-label study was to evaluate the safety and tolerability of AZD3043 after IV infusion and to estimate the maximal tolerated dose. Secondary objectives included the evaluation of AZD3043 pharmacokinetics, pharmacodynamics, and efficacy. Sequential ascending-dose cohorts of 5 or 6 healthy male volunteers aged 18 to 45 years received a single 30-minute IV infusion of AZD3043. Assessments included adverse events, vital signs, blood gases, laboratory values, clinical signs of sedation/anesthesia, and bispectral index. RESULTS: Fifty-three subjects received AZD3043 in infusion rate cohorts of 1, 3, 6, 12, 18, 27, 36, 54, and 81 mg/kg/h. There were no discontinuations, and dose escalation was stopped on reaching the predefined exposure limit. Adverse events occurring in >1 subject were headache ( n = 4), erythema ( n = 3), chest discomfort ( n = 2), nausea ( n = 2), and dyspnea ( n = 2). The frequency and character of adverse events appeared unrelated to dose. There were no spontaneous reports of pain on injection and no clinically relevant changes in respiratory rate or arterial blood pressure. However, heart rate increased dose-dependently at infusion rates >18 mg/kg/h. Occurrence of sedation/anesthesia corresponded with dose; the lowest applied infusion rate to induce anesthesia according to clinical signs of sedation/anesthesia at predefined time points was 12 mg/kg/h (1 of 6 subjects anesthetized), and all subjects in the 3 highest dose groups were anesthetized. The onset of anesthesia ranged from 4 minutes in the highest infusion rate group to 29 minutes in the 12-mg/kg/h infusion rate group. Return of response to oral command occurred at 3 minutes after the end of infusion in the single subject who was anesthetized in the 12-mg/kg/h group and median 25 minutes in the 81-mg/kg/h group. Involuntary movements ranging from minor twitches to extensive movements were accompanied by increased muscle tone. CONCLUSIONS: AZD3043 was well tolerated in this first human study and seems to exhibit rapid onset and recovery, indicating potential use as a short-acting drug for anesthesia and sedation. Abstract : Supplemental Digital Content is available in the text.Published ahead of print June 23, 2015